Labor market effects of trade and FDI: Recent advances and research gaps - Michael P. Pflüger; Uwe Blien; Joachim Möller; Michael Moritz (Institute for the Study of Labor (IZA), 2010)
This paper pursues three aims. First, we provide a review of current theoretical advances which pertain to the relationship between trade, FDI and labor markets. We do so under the following (not mutually exclusive) headings: (1) slicing-up the value added chain and the turn to a task-based approach, (2) firm heterogeneity and labor markets, (3) complex offshoring (integration) and sourcing strategies and (4) location of firms and labor markets. Second, we overview existing empirical work covering the labor market effects of trade and FDI. Finally, we identify and summarize the existing research gaps and thereby we highlight promising avenues for future research.
Keywords: F16; F23; R12; J60; 330; offshoring; outsourcing; FDI; trade; labor markets; agglomeration